Pengaruh Person Job Fit dan Person Organization Fit terhadap Komitmen Organisasional dan Organizational Citizenship Behavior (OCB): - Ananda, Dhea Nickita; Nasution, Aulia Arief; Syafi'i, Indra (Jurnal Ekonomi Bisnis Digital, 2022)
This study intends to examine the effect of person job fit on organizational commitment and organizational citizenship behavior (OCB), and see the effect of person organization fit on organizational commitment and organizational citizenship behavior (OCB). The researcher conducted a research at the Ministry of PUPR, Directorate General of Water Resources, Sumatra II River Basin Center. The number of population in the company is around 400 people, while the sample used by the researcher is 200 people using the Slovin formula method. Data was collected by distributing questionnaires. The results of this test indicate that person job fit has a positive and significant relationship to organizational commitment and organization citizenship behavior (OCB), while person organization fit does not have a positive and significant relationship to organizational commitment and organization citizenship behavior (OCB). The purpose of this research is to help organizations recruit, screen and place workers who want to join the organization carefully, so that the organization has quality human resources so that it can achieve the main goals of an organization.